Efficacy of Steinernema feltiae Nematode Against Lesser Mealworm (Alphitobius diaperinus) Populations from Poultry Farms in Türkiye - Burak Polat; Aysegul Cengiz; Samed Koc; Sevval Kahraman Kokten; Zeynep Nur Gultekin; Cansu Caliskan; Serap Kocaoglu Cenkci; Tolga Yildirim; Ozge Tufan-Cetin; Huseyin Cetin (Veterinary Sciences)
In the veterinary field, particularly in the poultry farming sector, Alphitobius diaperinus (Panzer, 1797) (Coleoptera: Tenebrionidae) is a significant pest that causes economic losses and acts as a vector for various pathogens. This study is the first to evaluate the efficacy of the entomopathogenic nematode Steinernema feltiae Filipjev, 1934 against both the larval (fifth instar) and imago (adult) of A. diaperinus from various Turkish populations. The insects were collected from six poultry farms in the provinces of Balikesir, Bolu, Canakkale, Manisa, and Izmir in Türkiye, bred, and then tested at concentrations ranging from 25 to 200 infective juveniles (IJs) per milliliter. Mortality was monitored over a five-day period. The findings revealed that larvae were much more susceptible to S. feltiae nematodes compared to adults, with LC50 values of larvae ranging from 33.17 to 83.12 IJs/mL. The Manisa population was the most susceptible, while the Izmir population was the most resistant. These results suggest that S. feltiae could be an effective biological control agent for managing A. diaperinus in Turkish poultry farms, reducing the reliance on chemical insecticides.